Pengaruh Kompetensi Sumber Daya Manusia Manusia dan Burnout Terhadap Kinerja Karyawan (Studi Kasus di CV Asih Suminar) - Arya Karmila; Niken Widyastuti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Every company formed has a vision and mission that must be carried out to achieve goals. To achieve the goals to be achieved, competent human resources are needed in their respective fields. However, nowadays many people are not working according to their competence because they are looking for income. While working, it is undeniable that employees will feel anxious and lead to burnout. Employee performance will go well if they have the same competence as their job and also do not feel burnout. The purpose of this study was to determine the effect of human resource competence and burnout on employee performance at CV Asih Suminar. In this study involved 30 respondents using descriptive qualitative research. Data collection is done by interviews, observation and documentation. With the result that competence lacks influence while burnout has an influence on performance.